2021
DOI: 10.3390/antiox10030470
|View full text |Cite
|
Sign up to set email alerts
|

Reprograming of Tumor-Associated Macrophages in Breast Tumor-Bearing Mice under Chemotherapy by Targeting Heme Oxygenase-1

Abstract: Tumor-associated macrophages (TAMs) represent one of the most abundant components of the tumor microenvironment and play important roles in tumor development and progression. TAMs display plasticity and functional heterogeneity as reflected by distinct phenotypic subsets. TAMs with an M1 phenotype have proinflammatory and anti-tumoral properties whereas M2-like TAMs exert anti-inflammatory and pro-tumoral functions. Tumor cell debris generated during chemotherapy can stimulate primary tumor growth and recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The results showed that macrophage clearance alone and Sanguinarine treatment alone could inhibit tumor growth, (Figure 4B), manifesting in the smallest tumor (Figure 4C) and the lightest tumor (Figure 4D). The percentage of CD11b+F4/80+ macrophages significantly decreased in the spleen and tumor tissue treated with macrophage clearance (Figure S3 and Figures 4F, S6B, E), which is consistent with previous reports (38)(39)(40). In addition, the group treated with CLPs effectively decreased tumor size and load (Figures 4B-D), indicating that macrophages contribute to neoplastic progression.…”
Section: Sanguinarine Inhibits Tumor Growth and Angiogenesis In Mice ...supporting
confidence: 91%
“…The results showed that macrophage clearance alone and Sanguinarine treatment alone could inhibit tumor growth, (Figure 4B), manifesting in the smallest tumor (Figure 4C) and the lightest tumor (Figure 4D). The percentage of CD11b+F4/80+ macrophages significantly decreased in the spleen and tumor tissue treated with macrophage clearance (Figure S3 and Figures 4F, S6B, E), which is consistent with previous reports (38)(39)(40). In addition, the group treated with CLPs effectively decreased tumor size and load (Figures 4B-D), indicating that macrophages contribute to neoplastic progression.…”
Section: Sanguinarine Inhibits Tumor Growth and Angiogenesis In Mice ...supporting
confidence: 91%
“…Macrophages are a heterogeneous cell group with distinctive phenotypes and functions in complex microenvironments ( 26 ). Traditionally, these cells are divided into M1 (classically activated macrophage) and M2 types (alternatively activated macrophages) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the subthreshold inoculum model, instead of suppressing tumor growth, chemotherapy promoted tumor growth in small or dormant tumors via tumor-promoting debris [1,3]. Similarly, chemotherapygenerated tumor cell "debris" (apoptotic and necrotic cells and cell fragments) promotes cancer progression and metastasis via stimulating an eicosanoid-driven cytokine storm of pro-inflammatory and pro-angiogenic mediators [1,2,14,38,39,57,76], polarizing tumor-associated macrophages (TAMs) as well as inducing immunosuppression and limiting anti-tumor immunity [24,77,78]. Thus, new approaches to stimulate the clearance of tumor cell debris are urgently needed [1,21,40,[78][79][80].…”
Section: Chemotherapy-stimulated Cancermentioning
confidence: 99%